2016
DOI: 10.1016/j.cca.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing sepsis – The role of laboratory medicine

Abstract: Sepsis is the host response to microbial pathogens resulting in significant morbidity and mortality. An accurate and timely diagnosis of sepsis allows prompt and appropriate treatment. This review discusses laboratory testing for sepsis because differentiating systemic inflammation from infection is challenging. Procalcitonin (PCT) is currently an FDA approved test to aid in the diagnosis of sepsis but with questionable efficacy. However, studies support the use of PCT for antibiotic de-escalation. Serial lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
105
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(121 citation statements)
references
References 82 publications
4
105
0
12
Order By: Relevance
“…7B). IL-6 levels are increased in patients with infectious complications and are used clinically to provide a quantitative assessment of sepsis severity (42)(43)(44). Additionally, IL-6 levels correlate with the mortality rate in septic patients (45).…”
Section: Elevated Early Life Il-27 Compromises Immunitymentioning
confidence: 99%
“…7B). IL-6 levels are increased in patients with infectious complications and are used clinically to provide a quantitative assessment of sepsis severity (42)(43)(44). Additionally, IL-6 levels correlate with the mortality rate in septic patients (45).…”
Section: Elevated Early Life Il-27 Compromises Immunitymentioning
confidence: 99%
“…Given the limitations of the above-mentioned biochemical markers, a wide variety of new markers related to microbiological products or the host’s inflammatory immune response have been proposed over the last few years 17. However, none of these markers can be recommended as a unique criterion for the diagnosis of sepsis, and experts recommend to use a combination of parameters, that is, infection score.…”
Section: Introductionmentioning
confidence: 99%
“…The increased life expectancy of individuals (including those who are immune-compromised) and the surge seen with the utilization of invasive medical interventions are all important contributors to the high incidence of sepsis and its complications. International guidelines highlight the need for early identification of the condition and prompt implementation of the treatment, including antibiotics to reduce the serious consequences [8][9][10][11][12][13]. It has been observed that prompt administration of antibiotics and improve outcomes in patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%